2021
DOI: 10.2298/jsc201111013g
|View full text |Cite
|
Sign up to set email alerts
|

Subcritical water extraction of horse chestnut (Aesculus hippocastanum) tree parts

Abstract: Subcritical water extraction of horse chestnut (Aesculus hippocastanum) parts, such as seeds, seed shell, bark and leaves has been performed in a batch reactor at temperatures of 150, 200 and 250?C and extraction times of 5, 15 and 30 min. The obtained extracts were analyzed by spectrophotometric methods to determine the total phenols, total carbohydrates and antioxidant activity. Furthermore, the compounds detected in the extracts, such as triterpene saponins (escins), coumarin glycosides (esculin and fraxin)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The increase in antioxidant activity with temperature and reaction time was also reported by Jokić et al [36], where the maximum antioxidant activity of cocoa shell extract was determined at 220 • C and 75 min (91.69%). Similarly, high antioxidant activity (90.54%) was determined for the extract of chestnut seed shells obtained under subcritical water conditions (250 • C, 30 min), which was significantly higher than that of the extracts of chestnut seeds (54.15%) and chestnut leaves (40.39%) [38].…”
Section: The Antioxidant Activity Of Extractsmentioning
confidence: 84%
See 3 more Smart Citations
“…The increase in antioxidant activity with temperature and reaction time was also reported by Jokić et al [36], where the maximum antioxidant activity of cocoa shell extract was determined at 220 • C and 75 min (91.69%). Similarly, high antioxidant activity (90.54%) was determined for the extract of chestnut seed shells obtained under subcritical water conditions (250 • C, 30 min), which was significantly higher than that of the extracts of chestnut seeds (54.15%) and chestnut leaves (40.39%) [38].…”
Section: The Antioxidant Activity Of Extractsmentioning
confidence: 84%
“…The biodegradable foam thus produced was a promising material that could take the place of plastic products in the future [5]. Gagić et al also reported that the amount of carbohydrates (87.22 mg TCH/g shells) extracted from the shells of chestnut seeds was the highest at 200 • C and 15 min [38].…”
Section: Total Carbohydrates Contentmentioning
confidence: 92%
See 2 more Smart Citations
“…The presence of polyphenols in the leaves, seeds, flowers, and bark of horse chestnut has been reported in the literature but not in red horse chestnut because it is a less well-known species. According to the literature, the content of polyphenols is: in horse chestnuts leaves (7.81–24.48 mg/g FW) [ 11 ], seeds (24.24–70.40 mg/g FW) [ 12 ], flowers (8.17 mg/g) [ 13 ], and bark (363.58 mg/g FW) [ 14 ]. For medicinal purposes, fruits, seeds, and cortex are used.…”
Section: Introductionmentioning
confidence: 99%